2019
DOI: 10.7202/1061714ar
|View full text |Cite
|
Sign up to set email alerts
|

La réflexivité : entre l’expérience déstabilisante et le changement?

Abstract: Tous droits réservés © Faculté d'éducation, Université de Sherbrooke, 2019 Ce document est protégé par la loi sur le droit d'auteur. L'utilisation des services d'Érudit (y compris la reproduction) est assujettie à sa politique d'utilisation que vous pouvez consulter en ligne. https://apropos.erudit.org/fr/usagers/politique-dutilisation/ Cet article est diffusé et préservé par Érudit.Érudit est un consortium interuniversitaire sans but lucratif composé de l

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
3
0
4
Order By: Relevance
“…This means that the different rewritings were beneficial for the students (Colognesi & Lucchini, 2016;Lee, 2011). In addition, we showed that these portfolio rewrites allowed participants to document and conceptualize their practices (Hamilton, 2017;Loughran, 2014), make better connections between theory and practice (Altet et al, 2013), and find ways to improve their teaching practices (Chaubet et al, 2019;Waege & Haugalokken, 2013). In this sense, the writing of the portfolio indeed had a knowledge-weaving role (Hamilton, 2020).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…This means that the different rewritings were beneficial for the students (Colognesi & Lucchini, 2016;Lee, 2011). In addition, we showed that these portfolio rewrites allowed participants to document and conceptualize their practices (Hamilton, 2017;Loughran, 2014), make better connections between theory and practice (Altet et al, 2013), and find ways to improve their teaching practices (Chaubet et al, 2019;Waege & Haugalokken, 2013). In this sense, the writing of the portfolio indeed had a knowledge-weaving role (Hamilton, 2020).…”
Section: Discussionmentioning
confidence: 81%
“…Four criteria (Table 2) were used to measure the development of students' reflective competence, with reference to the aspects of reflective analysis (Chaubet et al, 2019): observe situations (Criterion 1: describe one's practices) from new angles, document them to understand their multiple facets (Criteria 2 and 3: make theory-practice links to give meaning and master concepts used) and identify, through progressive analysis, possible solutions and actions (Criterion 4: development over time).…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…En cause : la gestion concomitante de la multiplicité des tâches à assumer par le novice et les responsabilités associées. Les transformations profondes que connait notre société depuis le XX e siècle complexifient encore davantage la profession (Chaubet et al, 2019). L'enseignant doit, en effet, s'adapter aux changements technologiques et informationnels rapides et continus (Charlier et al, 2020) ; aux nouveaux défis sociétaux ; à l'hétérogénéité croissante du public scolaire provenant de la massification et de l'allongement des études (Rayou et Véran, 2017) ; ainsi qu'aux nouvelles politiques de l'éducation (Cattonar et Dupriez, 2019).…”
Section: Problématiqueunclassified
“…Il en perçoit, par ailleurs, peu l'intérêt (Altet, Etienne, Desjardins, Paquay et Perrenoud, 2013). De plus, l'exercice réflexif, devenu un incontournable de la formation (Chaubet, Kaddouri et Fischer, 2019) intégré aux stages et aux cours (Maubant, 2007), reste peu appris et ne fait pas nécessairement l' objet d'un accompagnement (Bocquillon et Derobertmasure, 2018).…”
Section: Contexte Et Problématiqueunclassified